2016
DOI: 10.1177/1479972316631135
|View full text |Cite
|
Sign up to set email alerts
|

Pain and its clinical associations in individuals with cystic fibrosis

Abstract: Pain is recognized as a clinical complication in cystic fibrosis (CF), but the prevalence, characteristics and clinical associations of this co-morbidity have not been systematically reviewed. Electronic searches of six databases were performed. For inclusion in phase 1, studies reported a pain prevalence rate in CF and/or its clinical associations. For phase 2, included studies reported the measurement properties of validity, reliability and responsiveness of an instrument assessing pain in CF. Two independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Chronic pain is common in patients with chronic lung disease [156,157] and CTSS activity has been linked to pain in several conditions. The inflammatory chemokine CX3CL1/fractalkine, associated with inflammatory lung diseases [158], is proteolytic cleaved by CTSS resulting in the promotion of pain signaling [50,159].…”
Section: Other Outcomesmentioning
confidence: 99%
“…Chronic pain is common in patients with chronic lung disease [156,157] and CTSS activity has been linked to pain in several conditions. The inflammatory chemokine CX3CL1/fractalkine, associated with inflammatory lung diseases [158], is proteolytic cleaved by CTSS resulting in the promotion of pain signaling [50,159].…”
Section: Other Outcomesmentioning
confidence: 99%
“…Some studies have utilized well-established assessment measures to evaluate pain in patients with CF [71][72][73][74]. Approximately 42-84% of patients with CF experience pain [75], with headache, abdominal, back, chest, and limb pain being the most commonly identified [71,73,75]. Pain is significantly related to decreased daily activity, altered quality of life, and interference with treatments [71][72][73]75].…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Approximately 42-84% of patients with CF experience pain [75], with headache, abdominal, back, chest, and limb pain being the most commonly identified [71,73,75]. Pain is significantly related to decreased daily activity, altered quality of life, and interference with treatments [71][72][73]75]. Chest pain, headaches, back, joint, and limb pain also occur in patients with CF [72,76,77].…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Previous studies of acute, chronic, and/or procedural pain in CF have suggested that it occurs frequently in both children 13,16,17,21 and adults, 12,15,16,18,19 with prevalence rates ranging from 6% to 94%. 29 Although younger age has been identified as a risk factor to contribute to pain during medical procedures in children with chronic diseases other than CF, 30 we could not detect any age-dependent differences in pain 16 were unable to find an association between age and prevalence of pain perception.…”
Section: Respiratory Culture Sampling-related Painmentioning
confidence: 64%